A review of methods to assess coactivation in the spine. (February 2017) - Le, Peter; Best, Thomas M.; Khan, Safdar N.; Mendel, Ehud; Marras, William S.
Abstract: Coactivation is an important component for understanding the physiological cost of muscular and spinal loads and their associations with spinal pathology and potentially myofascial pain. However, due to the complex and dynamic nature of most activities of daily living, it can be difficult to capture a quantifiable measure of coactivation. Many methods exist to assess coactivation, but most are limited to two-muscle systems, isometric/complex analyses, or dynamic/uniplanar analyses. Hence, a void exists in that coactivation has not been documented or assessed as a multiple-muscle system under realistic complex dynamic loading. Overall, no coactivation index has been capable of assessing coactivation during complex dynamic exertions. The aim of this review is to provide an understanding of the factors that may influence coactivation, document the metrics used to assess coactivity, assess the feasibility of those metrics, and define the necessary variables for a coactivation index that can be used for a variety of tasks. It may also be clinically and practically relevant in the understanding of rehabilitation effectiveness, efficiency during task performance, human-task interactions, and possibly the etiology for a multitude of musculoskeletal conditions.